2014
DOI: 10.1152/jn.01071.2012
|View full text |Cite
|
Sign up to set email alerts
|

Spatial constant equi-affine speed and motion perception

Abstract: The two-thirds power law, postulating an inverse local relation between the velocity and cubed root of curvature of planar trajectories, is a long-established simplifying principle of human hand movements. In perception, the motion of a dot along a planar elliptical path appears most uniform for speed profiles closer to those predicted by the power law than to constant Euclidean speed, a kinetic-visual illusion. Mathematically, complying with this law is equivalent to moving at constant planar equi-affine spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 76 publications
(91 reference statements)
0
14
0
Order By: Relevance
“…The selected profiles were actually highly non-uniform, mimicking closely the kinematics of drawing movements in which instantaneous velocity and curvature covary according to the 2/3 Power Law [8]. This connection between visual perception and the velocity-curvature covariance has been confirmed for 2D [9] and 3D trajectories (where torsion also plays a role, [10]). Moreover, it has been shown that the 2/3 Power Law can be derived from the assumption that the equi-affine velocity of movements is constant [11][12].…”
Section: Introductionmentioning
confidence: 59%
“…The selected profiles were actually highly non-uniform, mimicking closely the kinematics of drawing movements in which instantaneous velocity and curvature covary according to the 2/3 Power Law [8]. This connection between visual perception and the velocity-curvature covariance has been confirmed for 2D [9] and 3D trajectories (where torsion also plays a role, [10]). Moreover, it has been shown that the 2/3 Power Law can be derived from the assumption that the equi-affine velocity of movements is constant [11][12].…”
Section: Introductionmentioning
confidence: 59%
“…Kinematic MPs are seen in a range of animal forms from soft-bodied muscular hydrostat effectors, to exoskeletons and endoskeletons. The commonalities in the kinematic operations of these very different effectors are likely to be geometric factors in visuomotor integration, see [49,50]. Analyses of the geometric factors continue to be explored, focusing on unifying features of affine geometries and links to dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…where a is a gain factor and _ x, _ y, € x, and € y are the first and second derivatives of x, y with respect to time. Important research from around the world 25,24 has demonstrated that in drawing trajectories, the gain factor a is approximately constant for simple elliptical shapes and piecewise constant for more complex patterns. 26,27 In addition, the affine speed v a for 2D movements, which is equal to the time derivative of the equi-affine arc-length, is defined by…”
Section: Two-thirds and One-sixth Power Lawsmentioning
confidence: 99%
“…22,23 Based on these results, it was demonstrated, that for 3D movements, the one-sixth power law explains the data better than the two-thirds power law. 22,24 In this article, affine speed is proposed as a feature to segment hand trajectories associated to medical training. In addition, energy calculation is introduced as a correlation measure to characterize hand skills.…”
Section: Introductionmentioning
confidence: 99%